2015
DOI: 10.1128/aem.03729-14
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacterial Blue Color Formation during Lysis under Natural Conditions

Abstract: dCyanobacteria produce numerous volatile organic compounds (VOCs), such as ␤-cyclocitral, geosmin, and 2-methylisoborneol, which show lytic activity against cyanobacteria. Among these compounds, only ␤-cyclocitral causes a characteristic color change from green to blue (blue color formation) in the culture broth during the lysis process. In August 2008 and September 2010, the lysis of cyanobacteria involving blue color formation was observed at Lake Tsukui in northern Kanagawa Prefecture, Japan. We collected l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 28 publications
0
42
2
2
Order By: Relevance
“…reported concentrations of α ‐ and β ‐ionone and 6,10,14‐ trimethyl‐decan‐2‐one derived from phytol, a derivative of chlorophyll. In A. platensis , β ‐carotene represented 67–79% of total carotenoids; therefore, the identification of β ‐cyclocitral as an AVOC was expected along with the identification of phytol and hydrocarbons as degraded compounds of chlorophyll and fatty acids . By contrast to previous publications, sulfur compounds were not detected …”
Section: Resultscontrasting
confidence: 57%
See 2 more Smart Citations
“…reported concentrations of α ‐ and β ‐ionone and 6,10,14‐ trimethyl‐decan‐2‐one derived from phytol, a derivative of chlorophyll. In A. platensis , β ‐carotene represented 67–79% of total carotenoids; therefore, the identification of β ‐cyclocitral as an AVOC was expected along with the identification of phytol and hydrocarbons as degraded compounds of chlorophyll and fatty acids . By contrast to previous publications, sulfur compounds were not detected …”
Section: Resultscontrasting
confidence: 57%
“…Different studies have reported algae and cyanobacteria volatile organic compounds (AVOCs) . Depending on the species and environmental conditions, the profile of these volatile organic compounds might change.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…and by the disruption of their cellular integrity (Suurnakki et al, 2015). In addition, because ␤-cyclocitral has lytic activity against cyanobacteria ( Arii et al, 2015), a high concentration of ␤-cyclocitral would accelerate the decomposition of the cyanobacteria in the bloom, further increasing the release of ␤-cyclocitral and VOSCs.…”
Section: Dynamics Of Taste and Odor Compounds In Black Bloommentioning
confidence: 99%
“…In rice paddies, the water is flooded during spring to summer and the water depth is less than 15 cm [21]. The water depth is more than 20 m in Lake Sagami and Lake Tsukui [22]. Therefore, these two Japanese lineages might have diverged rapidly in the two different habitats in Japan.…”
Section: Discussionmentioning
confidence: 99%